KARAKTERISTIK HABITAT DAN POPULASI TARSIUS (Tarsius fuscus Fischer 1804) DI RESORT BALOCCI, TAMAN NASIONAL BANTIMURUNG BULUSARAUNG, SULAWESI SELATAN - Abdul Haris Mustari; Fadhilah Iqra Mansyur; Dones Rinaldi (Media Konservasi, 2013)
Tarsier (Tarsius fuscus Fischer 1804) is one of endemic primates of South Sulawesi.  This species has been categorized as vulnerable by the International Union for Conservation of Nature (IUCN) Red List. This This study was conducted in Resort Balocci, Bantimurung Bulusaraung National Park from May to July 2011. The data collected were composition and structure of vegetations, number and diversity of insects, distribution and population size of tarsier. This study revealed that tarsier inhabited secondary forest, plantations and vegetation near settlement (yard). Nesting trees of tarsier could be observed in the crevices of the rocks, in the cracks of ficus trees (Ficus spp.), sugar palm tree (Arenga pinnata) and bamboos (Bambusa spp.). A total of 112, 89 and 80 individuals of insects recorded in the secondary forest, vegetation near the settlement and plantation respectively. A total of 13 groups consisting of 44 individuals of tarsiers recorded in the study area.  Of the 44 indvividuals encountered, 31 individuals, 9 individuals, and 4 individuals recoreded  in secondary forest, plantation, and vegetation near settlement respectively. Population densities of tarsier were 151 individuals/km2 in the secondary forest, 36 individuals/km2 in the plantation and 23 individuals/km2  in the vegetation near the settlement. Keywords : Tarsius fuscus, habitat, population, Bantimurung Bulusaraung National Park